Characteristic analysis of acoustic emission monitoring parameters for crack propagation in UHPC-NC composite beam under bending test. (5th April 2021) - Li, Shengli; Zhang, Longguan; Guo, Pan; Zhang, Pu; Wang, Chao; Sun, Wencong; Han, Shanling
Highlights: A new type of UHPC-NC beam is designed. Several AE parameters are used for monitor the crack propagation. The optimal AE monitoring parameters are selected. AE monitoring can be an alternative to traditional methods. Abstract: Ultra high performance concrete (UHPC) has more outstanding mechanical properties and durability than normal concrete (NC) materials. Currently, analysis methods for the mechanical properties of UHPC structures and UHPC composite structures, such as measuring structural deflection, strain, and observing crack propagation, are relatively single. Acoustic emission (AE) technique is a non-destructive testing method that evaluates the damage state of structures effectively. The variation characteristics of AE parameters can be used to analyze the damage process and the failure precursor information of the structures. On this basis, AE technique was used to monitor the crack propagation of the UHPC-NC composite beam under four-point bending test in this study. Results showed that the U-shape UHPC layer gave full play to its high strength and ductility characteristics under bending, which was mainly manifested in reducing the number and width of cracks of the UHPC-NC composite beam, reducing the mid-span deflection and increasing the cracking load (Pcr ) and ultimate load (Pu ). AE ringing counts, energy, and b-value showed different and easily distinguishable variation characteristics at each failure stage of UHPC-NC composite beam and can be considered the optimal AE monitoring parameters. RA-AF association analysis can be used to further analyze the failure mode of UHPC-NC composite beam. AE monitoring method can be considered an alternative to traditional monitoring methods for the real-time monitoring of crack propagation in UHPC-NC composite beams.